Legal regulation of artificial intelligence: international experience - Ennan, Ruslan; Еннан, Руслан Євгенович; Еннан, Р. Є. (Одеса : Фенікс, 2026)
As of today, the scientific and legal approach to understanding and regulating artificial intelligence is implemented either in the form of software (virtual platform, chatbots, programs, etc., which do not have a material form), or material objects (robots, drones, etc.), which act as tools for achieving specific goals set within the framework of legal relations. Since artificial intelligence is the result of human intellectual technological activity, as it is a human-designed device or computer program, there is every reaso to consider its legal nature from the perspective of intellectual property law. Analyzing the prospects for legal regulation of artificial intelligence under EU law, it can be noted that the development of European legal standards for robotics and artificial intelligence will contribute to the development of the relevant industry and ensure compliance with human rights when forming new social relations with the participation of autonomous devices.
Ennan R. Legal regulation of artificial intelligence: international experience. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 232-235. URL: https://doi.org/10.32837/11300.33094
Keywords: штучний інтелект; цифровізація; право інтелектуальної власності; правове регулювання; міжнародний досвід; artificial intelligence; digitalization; intellectual property law; legal regulation; international experience